Gli accessi chirurgici alla spalla - De Biase, P.; Biancalani, E.; Cortonesi, G.; Martinelli, D. (Lo Scalpello - Journal, 2018)
SURGICAL APPROACH TO PROXIMAL HUMERUSThe shoulder’s traumatology in recent decades has seen a major increase in surgical compared to conservativetreatment even if recent studies and meta-analyzes do not confirmed that surgical treatment leads to better functionalresults. The interest in the surgical accesses, expecially in mininvasive surgery, for the treatment of fractures of theproximal humerus had a new birth. The aim of this work is to illustrate the most commonly used surgical techniquein traumatology of proximal humerus.